2007
DOI: 10.1308/003588407x183355
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Routine Use of Venous Photoplethysmography in a One-Stop Vascular Surgery Clinic

Abstract: INTRODUCTION The decision to offer surgical treatment for varicose veins should be based on objective evidence of venous dysfunction and not only the subjective appearance or the reported symptoms. Special tests are required to identify the subgroup of patients with functional superficial venous reflux accurately. The initial test should be simple, cheap, objective, sensitive and easy to perform by a wide range of staff in order to screen out patients without reflux. The final test should be anatomically speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…5,8,10,24,25 The Pain Matcher pain threshold measurements in women with CVI are consistent with previous studies that reported lower thresholds in women with chronic pain, 21,26 acute oral pain, 11 or whiplash pain disorders 12 than in healthy individuals. 5,8,10,24,25 The Pain Matcher pain threshold measurements in women with CVI are consistent with previous studies that reported lower thresholds in women with chronic pain, 21,26 acute oral pain, 11 or whiplash pain disorders 12 than in healthy individuals.…”
Section: Discussionsupporting
confidence: 89%
“…5,8,10,24,25 The Pain Matcher pain threshold measurements in women with CVI are consistent with previous studies that reported lower thresholds in women with chronic pain, 21,26 acute oral pain, 11 or whiplash pain disorders 12 than in healthy individuals. 5,8,10,24,25 The Pain Matcher pain threshold measurements in women with CVI are consistent with previous studies that reported lower thresholds in women with chronic pain, 21,26 acute oral pain, 11 or whiplash pain disorders 12 than in healthy individuals.…”
Section: Discussionsupporting
confidence: 89%
“…A venous PPG is a sensitive, objective test providing information about venous pressure (AVG). Beraldo et al 14 described the possibility of using PPG in assessing the vascular bed. Similar studies were performed by Jasinski et al 2 in females with a diagnosed peripheral arterial disease.…”
Section: Discussionmentioning
confidence: 99%
“…It uses infrared light emission to the dermis, acting by reflecting off the cellular components and returning to the sensor. 14 17 The aforementioned studies report the use of reography in venous diseases, specifically venous reflux. The work of the VP in lower extremities is extremely important in assisting drainage of venous blood from the lower extremities, thus preventing blood retention and reflux.…”
Section: Introductionmentioning
confidence: 99%
“…Faster refill time is associated with impaired venous blood flow. VRT gives information about the overall function of the venous system and lacking among the studies of the therapeutic effects of surgery, compression therapy and exercise is cryotherapy (Beraldo et al. 2007).…”
Section: Discussionmentioning
confidence: 99%